2007
DOI: 10.31899/hiv2.1017
|View full text |Cite
|
Sign up to set email alerts
|

Community-based approaches to prevention of mother-to-child transmission of HIV: Findings from a low-income community in Kenya

Abstract: The Horizons Program, in partnership with International Medical Corps (IMC) and Steadman Research Services International (SRSI), conducted an intervention study in Kibera, an urban slum in Nairobi, to determine what effect three different community-based activities had on utilization of key prevention of mother-to-child transmission (PMTCT) services. The interventions included moving services closer to the population via mobile clinics, as well as increasing psychosocial support through the use of traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, continued implementation of routine testing at ANC sites with PMTCT programming can rapidly improve coverage. The proportion of postpartum women reporting that they took an HIV test at an ANC visit in Kenya increased from 84% to 93% between 2004 and 2005, 8 and in Swaziland, this figure rose from 72% to 92% between 2006 and 2007. 15 In India, nearly three-quarters of HIV-positive women interviewed underwent HIV testing as part of their ANC, suggesting that HIV testing during ANC is making a notable contribution toward HIV testing among women of reproductive age.…”
Section: Training Of Staff On Postnatal Ward and Use Of Peer Educatormentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, continued implementation of routine testing at ANC sites with PMTCT programming can rapidly improve coverage. The proportion of postpartum women reporting that they took an HIV test at an ANC visit in Kenya increased from 84% to 93% between 2004 and 2005, 8 and in Swaziland, this figure rose from 72% to 92% between 2006 and 2007. 15 In India, nearly three-quarters of HIV-positive women interviewed underwent HIV testing as part of their ANC, suggesting that HIV testing during ANC is making a notable contribution toward HIV testing among women of reproductive age.…”
Section: Training Of Staff On Postnatal Ward and Use Of Peer Educatormentioning
confidence: 99%
“…In Kenya, self-reports of infant feeding practices at six weeks postpartum among women who were HIV-positive, HIV-negative, and of unknown HIV status indicated that most women were using a mixed feeding method, in marked contrast to the infant feeding recommendations. 8 Improving utilization and impact By the early 2000s, PMTCT pilot programs were in place, but they were reaching only a small proportion of HIV-positive pregnant women. 5 Implementation of PMTCT services at their most basic included HIV counseling and testing to identify HIV-positive women during ANC, provision of ARV prophylaxis to HIV-positive women and their exposed infants, and infant feeding information.…”
Section: -2002mentioning
confidence: 99%
See 1 more Smart Citation
“…With increased testing among pregnant women, it has become more common for those women to reveal their HIV status to another person. Horizons studies found that more than three-quarters of HIVpositive women surveyed in Botswana, India, Kenya, South Africa, and Swaziland [9,10,16,21,26], reported telling at least one person, most commonly a partner or husband, they were HIV-positive. This held constant despite wide differences in marriage rates in the study populations.…”
Section: High Rates Of Disclosure By Hiv-positive Womenmentioning
confidence: 99%